Application of Visilora Learning Media to Class II Student Room Building Material - Ainun Naja; Feny Rita Fiantika; Susi Hermin Rusminati (Formosa Journal of Sustainable Research, 2023)
The decline in students' enthusiasm for studying mathematics was the inspiration for this research. The use of media will make mathematics learning more interesting. Visiora learning media will be used as the medium. Visilora's learning materials in the form of spatial materials are media that utilize technological advances and are able to foster a pleasant classroom environment, especially in mathematics learning. This research aims to explain how class II students at SDN Kepuh Kuncian 1 apply and respond to the visilora learning media on the topic of constructing shapes. Descriptive techniques and a qualitative approach were used in this research. Student observations, interviews, and questionnaires asking for student responses are the methods used to obtain data. Students were given a survey to fill out to measure the effectiveness of using Visillora learning resources